2013
DOI: 10.1002/da.22143
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Exposure to Suicide Predict Suicide Attempt

Abstract: Exposure to suicidal behavior in a friend or family member poses risk equivalent to the risk posed by becoming severely depressed. Attending to such risks could benefit clinical practice with adolescence and public health suicide prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
3
46
0
1
Order By: Relevance
“…-Patient's family members -Hospital personnel [16] Tooth staining of infants due to iron drip just on the teeth -Pediatrician -Baby parents [17] Neglect of the foot hygiene [nail care and proper footwear] -Diabetic patients themselves -Family physicians [18] Forgetting care of long sleep apnea -The patient him/herself or his/her wife [14] Self-medication -The patient him/herself [19] *Hundreds of common examples can be brought to person's malpractices on their own health status.…”
Section: Unreasonable Request For Medical Diagnostic Tests Examplesmentioning
confidence: 99%
“…-Patient's family members -Hospital personnel [16] Tooth staining of infants due to iron drip just on the teeth -Pediatrician -Baby parents [17] Neglect of the foot hygiene [nail care and proper footwear] -Diabetic patients themselves -Family physicians [18] Forgetting care of long sleep apnea -The patient him/herself or his/her wife [14] Self-medication -The patient him/herself [19] *Hundreds of common examples can be brought to person's malpractices on their own health status.…”
Section: Unreasonable Request For Medical Diagnostic Tests Examplesmentioning
confidence: 99%
“…As was the case with the previous two sections, the majority of papers in this section (41-95.3%) reported positive associations between children's/adolescents' SSHB and that of multiple reference groups (Abrutyn & Mueller, 2014;Ali, Dwyer, & Rizzo, 2011;Bearman & Moody, 2004;Bjarnason & Thorlindsson, 1994;Borowsky, Ireland, & Resnick, 2001;Borowsky, Resnick, Ireland, & Blum, 1999;Brent, Kolko, Allan, & Brown, 1990;Chan et al, 2009;Corder, Page, & Corder, 1974;De Leo & Heller, 2004;Deliberto & Nock, 2008;Feigelman & Gorman, 2008;Fleming, Merry, Robinson, Denny, & Watson, 2007;Gex, Narring, Ferron, & Michaud, 1998;Grossman, Milligan, & Deyo, 1991;Hargus, Hawton, & Rodham, 2009;Harkavy-Friedman, Asnis, Boeck, & DiFiore, 1987;Hawton, Rodham, Evans, & Weatherall, 2002;Jegannathan & Kullgren, 2011;Laederach, Fischer, Bowen, & Ladame, 1999;Larsson & Ivarsson, 1998;Larsson & Sund, 2008;Lewinsohn, Rohde, & Seeley, 1994;Mars, Heron, Crane, et al, 2014;McMahon, Corcoran, Keeley, Perry, & Arensman, 2013;McMahon et al, 2010;Nanayakkara, Misch, Chang, & Henry, 2013;O'Connor, Rasmussen, & Hawton, 2009;O'Connor, Rasmussen, & Hawton, 2014;O'Connor, Rasmussen, Miles, & Hawton, 2009;Portzky, Audenaert, & van Heeringen, 2009;Portzky, de Wilde, & van Heeringen, 2008;Rew, Thomas, Horner, Resnick, & Beuhring, 2001;…”
Section: Positive Findingsmentioning
confidence: 99%
“…Nine papers with positive findings (22.0%) employed longitudinal designs. Adolescents' SSHB was predicted by the earlier SSHB of others, and in fact friends' or family members' suicide attempts were found to be amongst the strongest predictors of adolescents' future suicide attempts (e.g., Borowsky et al, 1999;Nanayakkara et al, 2013). One study suggested that boys may be more susceptible to the influence of friends, whilst girls are susceptible to that of both family and friends (Abrutyn & Mueller, 2014).…”
Section: Positive Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior suicidal behavior has repeatedly been identified as a key predictor of subsequent suicide (Borowsky et al 2001;Mann et al 1999;Miranda et al 2014;Nanayakkara et al 2013;Shaffer et al 1996). Multiple additional factors are implicated in risk for suicide among adolescents, including temperamental characteristics (e.g., impulsivity; Askénazy et al 2003), cognitive factors (e.g., hopelessness; Thompson et al 2005), and social factors such as family dysfunction (Prinstein et al 2000), low perceived social support (Kerr et al 2006), and the absence of relationships with trusted adults (Pisani et al 2013).…”
Section: Introductionmentioning
confidence: 99%